ANALISIS PERENCANAAN STRATEGIS TEKNOLOGI INFORMASI DENGAN PENDEKATAN SWOT PADA KOPERASI PROJAKOP - Payong, Yohanes (HOAQ (High Education of Organization Archive Quality) : Jurnal Teknologi Informasi, 2021)
Investment in information systems and information technology is quite expensive. The value of benefits obtained through investment in information systems and information technology must be measurable. Not a few organizations investing in information technology are not able to show the benefits of information systems and information technology both visible (tangible) and invisible (intangible). ProjakopMitra Sejahtera Cooperative as a producer cooperative places information technology as part of its business strategy. Information systems and information technology strategies at the Projakop Cooperative are needed to plan the use of technology and information systems that are in line with the cooperative's business objectives. Strategic planning of Information Systems/Information Technology (IS/IT) uses one of the internal business analysis approaches and IS/IT is carried out using SWOT tools. The results of the SWOT analysis can identify potential weaknesses, strengths, opportunities, and threats. The results of the SWOT analysis show that strength is at the very high level of management and management. But on the same side, there are staff/employees who have a weakness in the lack of creativity in optimizing the existing IS/IT facilities. This can be seen in the activities of staff/employees who use social media more during working hours instead of working on the business activities of the Projakop Cooperative. The results of other SWOT analysis have four categories as indicators by having each SWOT matrix for information systems and information technology strategies, including governance, infrastructure, human resources, and applications.